2012
DOI: 10.5539/ass.v9n1p9
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Conceptual Model Promoting Learners’ Ownership in an Online Learning Environment

Abstract: The purpose of this study was to explore the development of a conceptual model that promotes ownership in an online learning environment. It proceeds toward building a comprehensive online learning model that illustrates the interrelationship among learning motivation, cognition and meta-cognition. Those components can be employed into strategies to promote the learner ownership that is assumed to be an essential factor influencing learners' achievement. The main methods of the study were literature review abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In the decision-making process, this research identified five motivational factors that activate the nursing students’ cognitive processes of learning and influence the nursing students’ intentionality. 26 A systematic review and meta-analysis of psychological factors related to university students’ learning revealed a domain named ‘sources of motivation’, which represents a learner’s motivational reasons to engage in his/her learning process. 27 This domain was further divided into two categories—intrinsic and extrinsic motivations.…”
Section: Discussionmentioning
confidence: 99%
“…In the decision-making process, this research identified five motivational factors that activate the nursing students’ cognitive processes of learning and influence the nursing students’ intentionality. 26 A systematic review and meta-analysis of psychological factors related to university students’ learning revealed a domain named ‘sources of motivation’, which represents a learner’s motivational reasons to engage in his/her learning process. 27 This domain was further divided into two categories—intrinsic and extrinsic motivations.…”
Section: Discussionmentioning
confidence: 99%